Does Fiscal Equalization Lead to Higher Tax Rates? Empirical Evidence from Germany - Manuela Krause; Thiess Büttner (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
This paper explores the role of fiscal equalization as a driver of states' tax policy in Germany. We argue that fiscal redistribution of tax revenues provides an incentive for states to increase their tax rates. The analysis exploits differences in the degree of fiscal redistribution among the states over time. The results show a significant effect on tax policy: with full equalization of revenues from the real estate transfer tax the tax rate is about one percentage point higher than without.
Keywords: H20; H26; R38; 330